In vitro Propagation of Solanum capsicoides All. An Important Therapeutic Agent ’Kantakari’ - Anish, N.P.; Rajesh, M.G.; Elias, Jiby; Jayan, N. (Plant Tissue Culture and Biotechnology, 2011)
Shoot tip explants from in vitro germinated seedlings of Solanum capsicoides All. inoculated on MS containing 2 mg/l BA produced maximum shoot induction response (26 shoots per explant). Rooting of the microshoots (19.4 roots per explant) was obtained better in half strength of MS supplemented with NAA (0.5 mg/l). Well rooted plantlets were successfully hardened with 80 per cent survival rate. Key words: Solanum capsicoides, Propagation, Therapeutic agent D.O.I. 10.3329/ptcb.v20i2.6912 Plant Tissue Cult. & Biotech. 20(2): 179-184, 2010 (December)